Comparison of serology and molecular detection of common red cell antigens in multitransfused thalassemia major and sickle cell disease patients. (February 2020) - Shah, Avani; Patel, Parizad; Patel, Keyur; Patel, Binal; Jariwala, Keyuri; Sharma, Preeti; Mishra, Kanchan; Ghosh, Kanjaksha
Abstract: Background: Serological testing for extended RHCcEe, Kell, Kidd and Duffy blood grouping from multitransfused patients may not give correct blood grouping of the recipient. Hence molecular testing for these blood groups was compared with serological groups in a cohort of multitransfused thalassemia mjor and sickle cell anaemia patients. Objective: Molecular genotyping of antigens of Rh (D, C, c, E, e), Kell (K, k), Duffy (Fy a, Fy b ) and Kidd (Jk a, Jk b ) blood group antigens by PCR and PCR-RFLP methods and comparison of predicted genotypes with their serological phenotypes. Materials and methods: A cohort of multitransfused thalassemia and sickle cell anemia patient were serologically and molecularly tested for RHCc, RHEe, K, k Fy a, Fy b, Jk a and Jk b antigens and compared. Serological testing was done by tube agglutination and molecular testing was done either by allele specific PCR or by RFLP technique just before next transfusion. Results: In more than 80% of the cases recipient's molecular testing blood groups were at variance with serologically tested blood groups (p < 0.0001). Mixed field reactions in serological typing were common. In sickle cell anemia patients no discrepancy was found. Molecular technique results were checked by Sanger's sequencing. Discussion: Extended phenotyping in multitransfused thalassemia patients by serological technique often donot detect the exact red cell phenotype of the recipient and molecular techniques for such grouping is preferable, especially in multitransfused thalassemia patients where red cells from previous transfusions continues to be present in significant numbers whenever the testing is done.